PELATIHAN BRANDING PRODUK DI YAYASAN TUNAS ALAM BANTAR GEBANG BEKASI - Teguh Santosa (Develop: Jurnal Ekonomi Pembangunan, 2021)
Various problems such as decreased purchasing power of hydroponic red spinach chip products, product packaging are still very simple and the absence of a brand on the packaging, and lack of ability in branding strategies in product packaging, this is an idea Pengabdian Kepada Masyarakat (PKM) which makes it the challenge to solved and the solution was found to be applied at the Tunas Alam Mulia Foundation, the shortage of planting methods using hydroponic techniques was able to be resolved properly, it's just that the weakness is the lack of ability in the branding strategy carried out because so far the packaging of the product is still very simple and there is no brand on the packaging. The branding training program raises a weakness in terms of selling hydroponic red spinach chips products at the Tunas Alam Mulia Foundation and provides solutions to these problems and the activities or training that have been provided are very useful for them, broaden their horizons with a wide range, can even provide an overview for make better product in future